DARI IDE MENJADI AKSI: MODEL PENGABDIAN KEPADA MASYARAKAT UNTUK PENGUATAN KREATIVITAS, INOVASI, DAN LITERASI AI BERPUSAT PADA MANUSIA DALAM MENUMBUHKAN MINAT KEWIRAUSAHAAN BERKELANJUTAN SISWA SMA - Selvi Esther Suwu; Ika Suhartanti Darmo; Yohana F. Cahya Palupi Meilani; Isana Sri Christina Meranga; Zoel Hutabarat (Faculty of Economics and Business Universitas Pelita Harapan, 2026)
This community service (PkM, Pengabdian Kepada Masyarakat) article reports a youth entrepreneurship empowerment intervention for 16–18-year-old students at SMA Citra Kasih Jakarta (n=24). The program responds to two concurrent realities: (1) Indonesia’s creative economy is increasingly important for job creation, and (2) students’ growing reliance on generative AI risks weakening independent thinking and problem sensitivity. Four theoretical pillars guide the intervention: youth empowerment and entrepreneurial mindset; experiential learning and design thinking; (creative) self-efficacy as a driver of action; and UNESCO’s human-centered AI literacy. The intervention combined a 45-minute interactive session, guided discussion, a micro-challenge translating real problems into value propositions, and rapid prototyping using pipe-cleaners to practice iteration and feasibility. Evaluation used a post-activity survey (5-point Likert), facilitator observations, and a structured rubric assessing problem clarity, novelty, usefulness, feasibility, and sustainability sensitivity. Results show strong participant acceptance (means 4.46–4.58; SD 0.51–0.66) and six group prototypes with value statements; indicating early gains in problem-framing and confidence to ideate without letting AI replace human reasoning. The novelty lies in embedding human-centered AI literacy within a compact entrepreneurship learning design and providing a replicable logic model, worksheet template, rubric, and follow-up roadmap aligned with sustainability agendas.